LEGAL REGULATIONS FOR THE USE OF AI CHATGPT IN PREPARING THESES REGRADING COPYRIGHT AND ACADEMIC ETHICS - Jaylu Kosasih; Mochammad Tanzil Multazam (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: This study aims to analyze the legal framework governing the use of Artificial Intelligence (AI) tools, particularly ChatGPT, in the preparation of student theses, focusing on copyright and academic ethics. Method: The research employs a normative juridical approach with a statutory analysis, utilizing primary legal materials such as Law No. 12 of 2012 on Higher Education, Law No. 28 of 2014 on Copyright, Law No. 19 of 2016 on Electronic Information and Transactions (ITE), Government Regulation No. 4 of 2014 on the Implementation of Higher Education, PERMENDIKBUD No. 3 of 2020 on National Higher Education Standards, and Circular Letter of the Minister of Communication and Information No. 9/2023. Results: The findings show that the use of AI ChatGPT in academic writing is legally permissible as long as students comply with copyright laws, uphold academic integrity, and appropriately cite sources. Novelty: This study contributes to the academic and legal discourse by clarifying the ethical and regulatory boundaries for AI-assisted research, emphasizing responsible use of technology in maintaining originality and academic honesty.